Cryopreserved PBMCs can be used for the analysis of mitochondrial respiration and serve as a diagnostic tool for mitochondrial diseases - Korandová, Zuzana; Pecina, Petr; Pecinová, Alena; Koňaříková, Eliška; Tesařová, Markéta; Houštěk, Josef; Hansíková, Hana; Ptáčková, Hana; Zeman, Jiří; Honzík, Tomáš; Mráček, Tomáš (Analytical biochemistry, 2025)
Mitochondrial diseases are severe, inherited metabolic disorders that affect the paediatric population. They affect the functioning of mitochondrial oxidative phosphorylation (OXPHOS) apparatus either directly or indirectly. Since mutations in mtDNA are responsible for only 25 % of paediatric cases and next-generation sequencing does not always provide a conclusive diagnosis, the biochemical approach still represents a valuable tool in diagnostics. Mitochondrial defects can be identified in tissue biopsies (muscle or skin). However, they also often manifest in peripheral blood cells. We developed a protocol for isolation and cryopreservation of peripheral blood mononuclear cells (PBMCs) from 5 ml of children's blood using Ficoll centrifugation which can be utilised for subsequent functional measurements on thawed samples. Furthermore, we evaluated the diagnostic utility of the optimised high-resolution oxygraphy protocol using digitonin-permeabilized cryopreserved PBMCs on 47 samples from patients with confirmed or suspected mitochondrial disease. Overall, the diagnosis was confirmed in 72 % of cases, while the analysis of cryopreserved PBMCs provided a false negative outcome in 13 % of cases. Our study demonstrates a sensitive, fast, and non-invasive approach for the diagnostics of various types of mitochondrial disorders, especially those of nuclear genetic origin manifesting in paediatric patients.
Keywords: Glycolysis; Cell Respiration; OXPHOS; mitochondrie; Leukocytes, Mononuclear; Oxidative phosphorylation; kojenec; kryoprezervace; mladiství; Cryopreservation; leukocyty mononukleární; buněčné dýchání; mužské pohlaví; Mitochondrial Diseases; oxidativní fosforylace; Infant; Peripheral blood mononuclear cells; PBMC; dítě; Child; Oxidative Phosphorylation; Child, Preschool; ženské pohlaví; Humans; předškolní dítě; Mitochondria; Mitochondrial diseases; Respirometry; Diagnostics; Female; Adolescent; lidé; Male; mitochondriální nemoci